Skrining Fitokimia Ekstrak Kombinasi Daun Kecibeling (Strobilanthes crispa (L.) Blume) dan Daun Pepaya (Carica papaya L.) - Dedek Fitriani; Melindra Mulia (MASALIQ, 2025)
This study is motivated by the limited research on phytochemical screening of combined medicinal plant extracts, despite the significant potential of this approach in developing more effective and efficient herbal medicines. The objective of this research is to explore the presence of secondary metabolites in a combination extract of kecibeling leaves (Strobilanthes crispa (L.) Blume) and papaya leaves (Carica papaya L.). A qualitative method was employed, with leaf samples purposively collected from the Lima Puluh Kota Regency, West Sumatra. Data were obtained through phytochemical screening tests using specific reagents to detect alkaloids, saponins, flavonoids, tannins, phenolics, triterpenoids, and steroids, and were analyzed descriptively. The results revealed that the combined extract contained saponins, flavonoids, tannins, phenolics, and triterpenoids, while alkaloids and steroids were not detected. These findings support the theory of possible synergistic effects among secondary metabolites in combined extracts, particularly in enhancing the presence of compounds such as tannins that were not identified in single extracts. The study concludes that combining plant extracts can enrich the phytochemical profile. Its implications include contributing to the scientific literature on the potential of local plants and offering practical recommendations for researchers and the herbal industry to consider combination formulations in the development of natural medicinal products. Furthermore, this research opens opportunities for follow-up studies on the pharmacological activity and toxicity of the combined extracts.